Changes in bone marrow in malaria-a prospective study of 47 cases - Rastogi, Nupur; Rehman, Neha (International Journal of Research in Medical Sciences, 2017)
Background: Bone marrow aspiration done in cases of repeated fever, fever of unknown origin, pancytopenia to detect Malaria parasite in bone marrow. The study was undertaken to evaluate the role of bone marrow aspiration in establishing the etiology of Plasmodium vivax in cases of pancytopenia or thrombocytopenia in recurrent fever or fever of unknown origin. Methods: Patients of different age groups presenting with recurrent fever or fever of unknown origin with pancytopenia or thrombocytopenia from Jan 2015 to Oct 2017. Out of the 108 bone marrow aspirations abiding the above criteria 47 showed presence of Plasmodium vivax trophozoites in bone marrow. Results: The age of patients varied from 8 months to 65 years. 47 cases showed presence of Plasmodium vivax trophozoites, mainly with hyperplastic marrow showing normoblastic and megaloblastic hyperplasia, presence of hemophagocytosis in 6 cases and also 2 cases showing increase in plasma cells. Conclusions: Bone marrow aspiration studies are of vital importance in diagnosing malarial infection in endemic areas as being one of the cause of pancytopenia or thrombocytopenia.